Diminished Quality of Life and Physical Function in Community-Dwelling Elderly with Anemia - Thein, Mya (2009)
The occurrence of anemia in older adults has been associated with adverse outcomes including functional decline, disability, morbidity and mortality. It is not clear to what extent these outcomes are the result of the anemia or concurrent illness. We performed a cross-sectional, observational study to determine whether lower hemoglobin concentrations in older adults are associated with reduced health-related quality of life, functional status, depression, disability, and physical strength, independent of chronic disease. Three sites participated in this research; an academic geriatric practice, a hospital based geriatric out patient unit, and a community-based multi-specialty internal medicine group. Health-related quality of life and functional status were measured using the Short Form-36 Health Survey (SF-36) and the Functional Assessment of Chronic Illness Therapy-Anemia (FACIT-An). Disability and depression were assessed using the Instrumental Activities of Daily Living (IADL) and the Geriatric Depression Scale (GDS) questionnaires, respectively. Handgrip strength was used as a physical performance measure. Anemia was defined as hemoglobin < 13 g/dL for men or < 12 g/dL for women. The mean SF-36 physical health component summary scores were 38.9 (with anemia) and 44.1 (without anemia), (P < 0.001). Anemia was associated with greater fatigue (P < 0.001), lower handgrip strength (P = 0.014), increased number of disabilities (P = 0.005) and more depressive symptoms (P = 0.002). Multivariate regression analysis, adjusted for demographic and clinical characteristics, demonstrated strong associations for reduced hemoglobin, even within the “normal” range, and poorer health-related quality of life across multiple domains. Thus, anemia was independently associated with clinically significant impairments in multiple domains of health-related quality of life, especially in measures of functional limitation. Mildly low hemoglobin levels, even when above the WHO anemia threshold, were associated with significant declines in quality of life among the elderly.